Problematics of Implementing Child-Friendly School Programs in Preschool Institutions - Nurhasanah Bakhtiar; Afrida Afrida; Mastura Mastura; Rani Fitrah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to analyze the problems of implementing child-friendly school programs in pendidikan anak usia dini institutions. This study uses a qualitative approach, conducted in five Raudhatul Athfal in Pekanbaru City. The main informants of this study consisted of five heads of Raudhatul Athfal and supporting informants from officials of the Ministry of Religion and the Pekanbaru City Women's Empowerment and Child Protection Service. Data were collected through in-depth interviews and observations. Data analysis techniques were carried out with 4-stage qualitative analysis: collection, reduction, data analysis and conclusions. The results of this study indicate that the implementation of the child-friendly school program in pendidikan anak usia dini institutions still has many problems, namely: 1) Government support that is not yet optimal and uneven policies. 2) Lack of socialization and guidance. 3) Lack of understanding of teachers and education personnel about the concept of Child friendly School. 4) Lack of funds, 5) Lack of commitment from the leadership of the institution. 6) Unsupportive infrastructure. 7) Frequently transferred human resources, 8). Lack of cooperation and participation of parents and the community. The obstacles encountered can be overcome with several best practices, namely: 1) Commitment and making written policies. 2) Thinking positively to always innovate for the progress of the institution. 3) Proactive attitude and take the initiative to the relevant agencies. 4) Trying to fulfill facilities gradually according to ability continuouslyKeyword : Implementation, Child-Friendly Schools, Early Childhood Education Institutions.ABSTRAK. Penelitian ini bertujuan untuk menganalisis problematika implementasi progam sekolah ramah anak di lembaga pendidikan anak usia dini. Penelitian ini menggunakan pendekatan kualitatif, dilaksanakan di lima Raudhatul Athfal di Kota Pekanbaru. Informan utama penelitian ini terdiri dari lima kepala Raudhatul Athfal ditambah dengan informan pendukung dari pejabat Kementerian Agama dan Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kota Pekanbaru. Data dikumpulkan melalaui wawancara mendalam dan observasi. Teknik analisis data dilakukan dengan analisis kualitatif 4 tahapan: pengumpulan data, reduksi, analisis data dan kesimpulan. Hasil penelitian ini menunjukkan bahwa implementasi program sekolah ramah anak di lembaga pendidikan anak usia dini masih banyak ditemukan problematika, yaitu: 1) Dukungan pemerintah yang belum maksimal dan kebijakan yang tidak merata. 2) Kurangnya sosialisasi dan bimbingan. 3) Kurangnya pemahaman guru dan tenaga kependidikan tentang konsep sekolah ramah anak. 4) Kekurangan Dana, 5) Kurangnya komitmen dari pimpinan lembaga. 6) Infrastruktur yang tidak mendukung. 7) sumber daya manusia yang sering mutasi, 8). Kurang kerjasama dan partisipasi orang tua dan masyarakat. Adanya kendala-kendala yang ditemui, dapat diatasi dengan beberapa best practice, yaitu: 1) Komitmen dan membuat kebijakan tertulis. 2) Berpikiran positif untuk selalu melakukan inovasi untuk kemajuan lembaga. 3) Sikap proaktif dan jemput bola ke dinas terkait. 4) Berupaya memenuhi fasilitas secara bertahap sesuai dengan kemampuan secara berkesinambungan.Kata Kunci : Implementasi, Sekolah Ramah Anak, Lembaga pendidikan anak usia dini.